2023
DOI: 10.1111/epi.17669
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain: A possible fluid biomarker in the intrahippocampal kainic acid mouse model for chronic epilepsy?

Marie‐Laure Custers,
Maxime Vande Vyver,
Lea Kaltenböck
et al.

Abstract: ObjectiveIn the management of epilepsy, there is an ongoing quest to discover new biomarkers to improve the diagnostic process, the monitoring of disease progression, and the evaluation of treatment responsiveness. In this regard, biochemical traceability in biofluids is notably absent in contrast to other diseases. In the present preclinical study, we investigated the potential of neurofilament light chain (NfL) as a possible diagnostic and response fluid biomarker for epilepsy.MethodsWe gained insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…An important advantage of NfL is its reliability in measurement in serum/blood. Additionally, two studies on humans [63,65] and a preclinical study [60] have demonstrated a close and optimal correlation between the peripheral and central compartments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important advantage of NfL is its reliability in measurement in serum/blood. Additionally, two studies on humans [63,65] and a preclinical study [60] have demonstrated a close and optimal correlation between the peripheral and central compartments.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that the data obtained in preclinical animal models are mainly derived from the observation of alterations in different biomarkers on tissue and not on biological fluids, with some exceptions [30,60,78]. In this sense, on the one hand, it is important to be cautious in formulating parallels between humans and data in the animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation